Effect of drying temperature on the phytochemical and functional properties of muyuyo (Cordia lutea lam) flower extract (Agroindustria, Sociedad y Ambiente, 2026)
Plant species have been used since ancient times as part of traditional medicine due to their different biological properties. The research was carried out with the aim of characterising the phytochemical and functional components of the muyuyo flower (Cordia lutea Lam) by applying different drying temperatures. A completely randomised experimental design was used, evaluating the incidence of three drying temperatures (T1: 40°C; T2: 50°C and 60°C). The drying kinetics were determined as a function of time and temperature applied, to subsequently evaluate the presence of phytochemical components, antioxidants and antimicrobial activity of the extracts. The results with the ethanolic extract at 40 °C showed the highest antioxidant capacity with values of 2944.68 µmol TE/g (ABTS) and 5036.03 µmol TE/g (DPPH), which was significant according to Tukey's test (p
Keywords: antioxidants, dehydrated, secondary metabolites